Microlicia inconspicua (Melastomataceae: Lavoisiereae), an overlooked new species from the Chapada Diamantina, Bahia, Brazil - Pacifico, Ricardo [UNESP]; Almeda, Frank (Springer Nature, 2025)
A new species of Microlicia (Melastomataceae: Lavoisiereae), M. inconspicua, is described and illustrated from the campo rupestre of Bahia, Brazil. This species is compared to its presumed closest relatives, M. oligochaeta Wurdack and M. wurdackiana Almeda & A.B.Martins. Microlicia inconspicua is apparently restricted to the Serra da Batávia (Mucugê) and Serra do Barbado (Abaíra) in Bahia, where it grows in campo rupestre vegetation, exposed to full sun, at elevations between 1,200 and 2,000 m. Illustrations, photographs of the new species and a distribution map for M. inconspicua and related species are also provided.